Resistance Exercise For Enhancing Speed/Power Performance - Ioannidis , Chloe (My University, 1996)
Ten subjects were randomly assigned to train one arm with ballistic movements (BT), whereas the other arm trained with ballistic and heavy resistance movements (BT+HRT). The training program consisted of three training sessions per week, over a ten week period. The BT arm executed ten sets of six maximal ballistic elbow extension actions (10% MVC), whereas the BT+HRT arm executed five sets of six repetitions of maximal ballistic actions followed by five sets of five to eight repetitions of heavy resistance elbow extension actions. After training, evoked twitch contractile properties, ballistic, 1 RM, and isometric MVC measures were analyzed. Incorporated with all performance measures were EMG recordings of the agonist (AG) triceps and antagonist (ANT) biceps. Muscle biopsies of triceps were also taken to determine muscle fibre type composition, and fibre area. The BT+HRT arm demonstrated a significant decrease in the percent population of type IIb fibres (22% to 18. 8%). Furthermore, the BT+HRT arm produced hypertrophy, type IIa (6184 to 7086 μm²) and IIb (5714 to 6734 μm²) fibre areas increased, whereas type I fibre areas (3503 to 3828 μm²) did not significantly increase, after training. In contrast, the BT arm and control arm did not display fibre transformation or hypertrophy after training. Triceps evoked twitch peak torque increased for only the BT+HRT arm (12.5 to 13.8 N·m). Furthermore, the 1 RM increased significantly in the BT+HRT arm (~24%) but did not change significantly in the BT arm. However, ballistic and isometric MVC PT values increased similarly in both the BT (19.6 to 23.5 N·m; 45.4 to 52.6 N·m) and the BT+HRT (19.6 to 23.6 N·m; 49.6 to 56.0 N·m) arms. The EMG results corresponded to the performance results in that triceps AEMG in the 1 RM test tended to increased more after HRT (0.71 to 1.01 mV) than only BT (0.72 to 0.81 mV), but in the ballistic (HRT= 0.63 to 0.79 mV; BT= 0. 62 to 0. 73 mV) and isometric MVC performance measures (HRT= 0.80 to 0.84 mV; BT= 0.80 to 0.87 mV), the AEMG results were similar. Supplementary HRT caused muscle hypertrophy, particularly of the type II fibres, but did not promote improvement in ballistic performance with loads equal to or less than 10% of maximal isometric force.
The Role of High Resistance Exercise in Enhancing Speed/Power Performance
Keywords: high resistance exercise, exercise, speed, power, performance